PTU-018 Endoscopy: the effect of hospital anxiety and depression scale on patient experience. (17th June 2017) - Raju, SA; Marks, L; Ching, H-L; McAlindon, ME
Abstract : Introduction: The effect a patients baseline anxiety and depression has on their experience of oesophagogastroduodenoscopy (OGD) is unclear, as is how this affects their view of the service. We present a questionnaire study of patients undergoing OGD in our endoscopy department. Method: A closed ended questionnaire was given to adult patients attending outpatient OGD between November 2016 and January 2017. The patients hospital anxiety and depression scale (HADS), sedation requirement, expectations, experience of OGD and service evaluation were assessed in the questionnaire. Patients were asked to rank questions focused on unpleasant sensations (gagging, vomiting, choking and bloating), discomfort and pain. All patients were offered sedation with fentanyl and midazolam. Results: Questionnaires were completed by 100 patients: 46 female (med: 62 years±13.5 years), 54 male (med: 57±13 years). There was a significant difference in anxiety score (AS) between females and males (med: 7±3.15 vs 4.5±3.5 respectively p=0.001) and depression score (DS) (med: 5±3.5 vs 2±2.75 respectively p=0.026). Patients with a high AS or DS had statistically significantly greater concerns and expectations prior to OGD but no statistically significant difference in their experiences of unpleasant sensations or discomfort (Table 1). Patients with a higher AS and DS experienced statistically significantly more pain than those with lower scores. Sedated patients experienced less unpleasant sensations and discomfort. Conclusion: Patients with higher AS or DS have greater concerns prior to OGD. However, their actual experiences are no different to those with lower scores with regards to unpleasant sensations and discomfort. Sedated patients reported a better experience suggesting a beneficial role of sedation in reducing awareness of unpleasant sensations and discomfort. Disclosure of Interest: None Declared